Racism in Brazilian soccer: a bibliometric review in scientific journals Racismo en el fútbol brasileño: revisión bibliométrica en revistas científicas Racismo no futebol brasileiro: revisão bibliométrica em periódicos científicos - Beirith M.K.* (2024)
© 2024 Federacion Espanola de Docentes de Educacion Fisica. All rights reserved.There is a lack of reviews related to scientific production about racism in Brazilian football in journals in the present century. The present study aimed to map and explore the scientific production related to racism in Brazilian soccer in scientific journals in the 21st century. The study is characterized as a review, using bibliometrics. The articles were tracked in Web of Science, Scopus and Lilacs databases, using the equation in Portuguese Racism or Negr* or Pret* and Futebol and in English Racism or Black and Soccer or Football. The results consist of: 20 publications; 28 authors (mostly men); highlight to years 2020 and 2021; North and Midwest regions were not included; 15 Brazilian and one international institution have studies; most of the authors related to Physical Education and Human Sciences; emphasis on Physical Education journals; keywords related to soccer, racism and prejudice appear more often. These results express the increase in the scientific community's interest in the theme concomitant with the increase of the news and episodes of racism in Brazilian soccer and outline a new trend in research of the topic.